Global Communication in Public Health and Community Medicine: A Cross-cultural Perspective and Social Change - Nurhaya Muchtar (The Indonesian Journal of Community and Occupational Medicine, 2024)
This article discusses the importance of cross-cultural understanding in global health communication to achieve social change in community medicine and public health. The theories of Entertainment Education (EE) and Diffusion of Innovation (DOI) are utilized to promote behavioral change through mass media, particularly during the COVID-19 pandemic. The article highlights the importance of involving community members in health programs and addressing cross-cultural communication challenges. Additionally, it emphasizes the need for health communication training for practitioners and the understanding of public health complexities by communicators.